2017
DOI: 10.1177/0972150917713065
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Technical Efficiency and Income Inequality of Food Vending as a Family Business in Southwest Nigeria

Abstract: This study examines the determinants of technical efficiency (TE) and income inequality of family business in southwest Nigeria. Data were obtained from primary source using structured questionnaire and interview schedule. A multi-stage sampling technique was employed in selecting 120 respondents for the study. Analyses were carried out using descriptive statistics, Gini coefficient and Lorenz curve as well as the stochastic frontier production function models. The results revealed that experience, educational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…But, as reported by Anang et al (2016) where educated smallholder rice farmers in Northern Ghana were inefficient, and by Deressa et al (2017) where educational level of a household head has a negative effect on technical efficiency in potato production in Welmera district of Oromia Regional State, Ethiopia, higher educational attainment does not necessarily increase efficiency in all crops and all locations. However, the experience of the household head has a positive and significant effect on technical efficiency, not only in this study but also in other sub-Sahara African countries (Maganga, 2012;Olubukola et al, 2017).…”
Section: Discussionmentioning
confidence: 45%
“…But, as reported by Anang et al (2016) where educated smallholder rice farmers in Northern Ghana were inefficient, and by Deressa et al (2017) where educational level of a household head has a negative effect on technical efficiency in potato production in Welmera district of Oromia Regional State, Ethiopia, higher educational attainment does not necessarily increase efficiency in all crops and all locations. However, the experience of the household head has a positive and significant effect on technical efficiency, not only in this study but also in other sub-Sahara African countries (Maganga, 2012;Olubukola et al, 2017).…”
Section: Discussionmentioning
confidence: 45%
“…Linked to the current inquiry, to the best Discrete effects of family business exposure of the authors' knowledge, prior studies differentiating the types of FB exposure as background factors in Nigeria or other contexts are limited. Scholars have been interested in family businesses' strategic marketing practices (Omotayo, 2009), succession issues (Ogundele, 2012), professionalisation (Onuoha, 2012), characteristics (Banki and Ismail, 2015), seasonality (Banki et al, 2016), competitive advantage (Bednarz et al, 2017), technical inefficiency (Olubukola et al, 2017), cultural institutions (Igwe et al, 2018) and the performance of non-family members (Agbaeze et al, 2019). Thus, notwithstanding the substantial volume of research on family entrepreneurship in developing settings, capturing different facets of exposure to family business will advance the extant literature.…”
Section: Ijebr 286 1438mentioning
confidence: 99%
“…, 2016), competitive advantage (Bednarz et al. , 2017), technical inefficiency (Olubukola et al. , 2017), cultural institutions (Igwe et al.…”
Section: Introductionmentioning
confidence: 99%
“…There are various factors that affect income inequality such as demographics, political, cultural and environmental, and macroeconomics factor (Ezcurra, Pascual, & Rapun, 2007;Nangarumba, 2015;Olubukola, Olayemi, Adewale, & Silvester, 2017;Wulandari et al, 2017). Many researchers suggested that financial deepening can be seen as one of the factors that affects the income inequality.…”
Section: Introductionmentioning
confidence: 99%